PERSONALITY DIFFERENCES IN ADJUSTMENTS TO MILITARY AND ACADEMIC TRAINING AMONG CADETS OF THE NIGERIAN DEFENCE ACADEMY KADUNA - Ruwan, Ibrahim Ignatius Felix; Iliya, Vakpa; Okorie, Agnes O; Nanfort, Wakkias; Fadare, Gbenga Oba; Jose, Charlton (African Journal of Social and Behavioural Sciences, 2020)
The aim of this research was to investigate personality differences in adjustment to military and academic training among cadets of Nigerian Defence Academy Kaduna. The study used Quasi-Experimental Design. A total of two hundred cadets were selected for the study through Purposive and convenient sampling method. Eysenck Personality Questionnaire-Revised short version was used to collect data from participants. Data collected for this research were analyzed with simple percentage for demographic while ANOVA was used in testing hypothesis. The study found that NDA Cadets with adjustment records were significantly more extraverted, more neurotic and higher in psychoticism when compared with those without adjustment records. In conclusion, this study addressed a critical issue of adjustment to training by cadets in NDA. Apart from providing insights to adjustment of cadets and complementing existing studies on adjustment of trainees in military institutions, it has provided an African perspe tive to the global literature. Further researches are expected and encouraged in the ar a to include larger samples and variables.